Assessing Governance and Strengthening Capacity in Haiti - Carrillo, Susana (World Bank, Washington, DC, 2012)
This Capacity Development Brief explores the experience of describes some of the findings of the diagnostic, which was completed in 2006. The indicators measures of governance are: voice and accountability, rule of law, government effectiveness, regulatory quality, control of corruption, political stability, and absence of violence. The author have started to work to strengthen state structures and consider the legal and regulatory reforms needed in order for this endemic disease to disappear from our institutional practices, in politics as in business. Although Haiti's governance problems are fairly widespread, release of the survey has already started to have some impact, at least in terms of growing understanding and consensus on the nature of the problems the country faces. The survey served to focus minds on a set of critical areas that are impeding the country's economic and political stability.